Experience of providing eye care to the wounded at the NMMCC “Main Military Clinical Hospital” during the defense of Kyiv in February-April 2022 (Ukrainian Journal of Ophthalmology, 2023)
Background:  A full-scale Russian invasion of the territory of Ukraine required the military medical authorities to introduce corrections in the operation of the support system for treatment and evacuation of casualties with combat ocular trauma (COT). While the combat activities were taking place in Kyiv’s suburbs, the inpatient eye clinics of the city actively contributed to the provision of care to casualties.Purpose: To examine the results of the managing decisions made on the introduction of corrections in the operation of the support system for treatment and evacuation of casualties with COT on the basis of the comparative analysis of the efficacy of medical care provided to casualties at the eye clinic of the National Military Medical Clinical Center “Main Military Clinical Hospital” (NMMCC “MMCH”).Material and Methods: We presented the results of the analysis of (a) changes in the pattern and amount of treatment and diagnostic interventions provided to casualties in different time periods related to changes in the tactical combat situation and (b) transformation in the levels of provision of medical care to casualties with COT that took place due to the above changes. The structure of causes and locations of ocular and ocular adnexal injuries was calculated based on the aggregated data from medical papers related to treatment of combat casualties at the eye clinic of the NMMCC “MMCH” during 2014-2021 and February-April 2022. System, comparative and content analysis methods, descriptive modeling, statistical analysis and principal methods of treatment and diagnosis of eye disease were used as methods of the study.Results: It was demonstrated that the urgent corrections introduced in the conventional four-level system of medical and evacuation support during combat activities in the metropolitan suburbs of Kyiv were timely and adequate. We reviewed the changes in the pattern of COT in different periods of combat activities on the territory of Ukraine and indentified the issues requiring primary consideration in order to remove the shortcomings in the organizational support of the treatment and evacuation of casualties with COT.Conclusion: First, the results of our comparative analysis of the advanced support system for treatment and evacuation of casualties under combat actions in aggravated tactical situations (particularly, during the defense of the metropolitan area of Kyiv), demonstrated the efficacy of the algorithms and standards recommended by NATO. Second, the front line advancing to the outskirts of the metropolitan area required making urgent managing decisions on introducing corrections in the classical four-level support system for treatment and evacuation of casualties (particularly, those with COT), which caused the NMMCC “MMCH” to unite and coordinate their care efforts with those of the special medical facilities of the metropolitan area of Kyiv. There were changes in the amount of eye care provided, with a change to level 3 and subsequently in the opposite direction to level 4, within a very short period, which did not cause difficulties for the military medical personnel. Third, combat actions at the outskirts of the metropolitan area of Kyiv resulted in an increase in the percentage of the wounded with combat-related injuries of the eye and adnexa to 9.4% of the total number of wounded, with more than half (54%) of them represented by penetrating injuries, particularly those with an intraocular foreign body (43.3%). The percentage of binocular injuries and eye destruction increased to 29.8% and the percentage of multiple combat-related injuries to 81.4%, likely primarily due to wide use of high-kinetic-energy weapons with high-velocity fragments from explosive munitions of these systems having wide-area effects. Fourth, we found that treatment outcomes were better when casualties with COT (a) had an early single-stage evacuation to the destination point and (b) were timely provided with special care, which is especially important in bilateral severe eye injuries with a threat of irreversible visual function loss. Finally, the identified problems and shortcomings were causeded primarily by impaired logistics of the support of treatment and evacuation of casualties, and shortage of medical staff (particularly, specialty doctors), medications and medical supplies, particularly at the territories which external communications were temporarily blocked.
Keywords: combat ocular trauma; levels of the support system for treatment; evacuation of casualties